After-hours medical deputising services: patterns of use by older people - Joe, A.; Lowthian, J.; Shearer, M.; Turner, L.; Brijnath, Bianca; Pearce, C.; Browning, C.; Mazza, D. (Australasian Medical Publishing, 2016)
OBJECTIVES: To examine how older people use an after-hours medical deputising service that arranges home visits by locum general practitioners; to identify differences in how people who live in the community and those who live in residential aged care facilities (RACFs) use this service. DESIGN, SETTING AND PARTICIPANTS: Retrospective analysis of routinely collected administrative data from the Melbourne Medical Deputising Service (MMDS) for the 5-year period, 1 January 2008 - 31 December 2012. Data for older people (= 70 years old) residing in greater Melbourne and surrounding areas were analysed. MAIN OUTCOME MEASURES: Numbers and rates of MMDS bookings for acute after-hours care, stratified according to living arrangements (RACF v community-dwelling residents). RESULTS: Of the 357 112 bookings logged for older patients during 2008-2012, 81% were for RACF patients, a disproportionate use of the service compared with that by older people dwelling in the community. Most MMDS bookings resulted in a locum GP visiting the patient. During 2008-2012, the booking rate for RACFs increased from 121 to 168 per 1000 people aged 70 years or more, a 39% increase; the booking rate for people not living in RACFs increased from 33 to 40 per 1000 people aged 70 years or more, a 21% increase. CONCLUSIONS: After-hours locum GPs booked through the MMDS mainly attended patients living in RACFs during 2008-2012. Further research is required to determine the reasons for differences in the use of locum services by older people living in RACFs and in the community.